The Effect of Restriction Style On the Meaning: Theory And Practice/ أثر أسلوب القصر في المعنى بين النظرية والتطبيق - Fehmieh R. Nawaya; Ahmad S. Burhan; Ali M. Asaad; Zakaria H. Habeeb Alkhulee (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The restriction style is a rhetorical style that has a significant effect on the meaning. This research aimed to investigate the identification between the theoretical effects of the restriction style as mentioned in the rhetoric books compared to its practical effects as found in the interpretation of al-Mufassal Surahs. The research followed the descriptive-analytical approach by the complete induction of different restriction methods in al-Mufassal Surahs. For the extracted restriction examples, the pillars and types of the restriction style have been determined according to the theoretical rules. Then these elements have been compared with what was stated in the interpretation of the examples. Results: The restriction style is reported in 352 locations of al-Mufassal Surahs including the restriction with some tools indicating it by the linguistic situation and the restriction with understandable verbal semantics by the content. The context had a critical role in determining the meaning of the restriction sentence. In addition to the context of the verse studied, the restriction style with its various methods relates to the context of this verse with its previous and next one. Also, each method of the restriction style is used in special locations and conditions. Although those methods share the meaning of restriction, there are essential differences between them, so it is not appropriate for one to be replaced with another. Moreover, the restriction style with its studied methods had a role in the argumentation because the sentence of restriction had a definitive and improbable significance that reflects the will of the speaker; thus, it affects the recipient. The research found that the practical effects of the restriction style go beyond the theoretical effects, which were limited to the meaning of the restriction. However, three ways enabled the restriction style to express the meanings in al-Mufassal Surahs interpretation. The first: is the clarification of meaning, in which the restriction style comes to highlight the basic meaning of the sentence. The second: reinforcing the meaning, in which the restriction style strengthens the characteristics of what is being talked about, whether they are positive or negative. The third: is adding new meanings. The restriction style adds other meanings to the meaning of restriction.